2017
DOI: 10.1097/txd.0000000000000638
|View full text |Cite
|
Sign up to set email alerts
|

Application of Operational Tolerance Signatures Are Limited by Variability and Type of Immunosuppression in Renal Transplant Recipients: A Cross-Sectional Study

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 45 publications
(61 reference statements)
2
28
0
Order By: Relevance
“…Recent data suggest that the type and dose of immunosuppressive therapy may interfere with the induction of CD19 + CD24 hi CD38 hi transitional B lymphocytes (Bregs) (21,22). In a crosssectional study of 117 transplant recipients, Bottomley et al found no significant association between steroids and Bregs (21), whereas in the Genetic Analysis of Molecular Biomarkers of Immunological Tolerance (GAMBIT) study, Rebollo-Mesa et al observed slightly higher Breg percentages in patients with reduced or no steroids (22). To address this issue, we identified transplanted control patients on immunosuppressive therapy comparable to that for MIC-treated patients and analyzed their Breg frequencies retrospectively.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data suggest that the type and dose of immunosuppressive therapy may interfere with the induction of CD19 + CD24 hi CD38 hi transitional B lymphocytes (Bregs) (21,22). In a crosssectional study of 117 transplant recipients, Bottomley et al found no significant association between steroids and Bregs (21), whereas in the Genetic Analysis of Molecular Biomarkers of Immunological Tolerance (GAMBIT) study, Rebollo-Mesa et al observed slightly higher Breg percentages in patients with reduced or no steroids (22). To address this issue, we identified transplanted control patients on immunosuppressive therapy comparable to that for MIC-treated patients and analyzed their Breg frequencies retrospectively.…”
Section: Discussionmentioning
confidence: 99%
“…Edward Geissler, David Sachs, and Kenneth Newell. There was a consensus that graft injury and loss in these trials should be no greater than in standard of care patients, and prevention can be improved by use of biopsies just before drug minimization, and the use of biomarkers of tolerance [14][15][16][17][18][19][20][21][22][23][24] .…”
Section: Discussion Of Immunosuppressive Drug Minimization and Of Dismentioning
confidence: 99%
“…The relative proportions of these distinct morphologic and presumably molecular phenotypes in any data set will affect any putative disease-associated transcriptome signatures that can be derived from these tissues. In the study by Sigdel et al, 9 , 54 an attempt was made to match BKPyVN and control biopsies for major clinical variables such as donor/recipient age, % living donor kidneys, time posttransplant, and immunosuppression usage. However, there were insufficient numbers of BKPyVN biopsies to separately study individual disease phenotypes.…”
Section: Discussionmentioning
confidence: 99%